Strategi Pembelajaran Berbasis Kearifan Lokal - Amna Emda; Suriana; Mukhlis; Nafisah Hanim (JKA, 2024)
In the era of globalization, the education system is faced with the challenge of preparing learners not only to meet the needs of the job market but also to preserve local cultural identity. Locally based wisdom learning is an approach that integrates local values and knowledge into the content and learning process. This research utilizes a qualitative approach to describe the strategies for implementing locally based wisdom learning. The results of the research indicate that this approach can be applied through various strategies, such as project-based learning, discovery learning, and the integration of local wisdom values into the learning content. Locally based wisdom learning has several advantages, including helping students understand academic concepts by relating them to the local cultural context, instilling local cultural values, and encouraging students to appreciate and preserve local culture. Thus, this approach offers an effective solution to the challenges of globalization while maintaining cultural diversity.